Genome sequencing reveals novel variants in a diverse population with congenital anterior segment anomalies - Ashraf Hussain; Maria Fernanda Villalba; Dayna Morel Swols; Rayan Abou Khzam; Brittney Keira Johnson; LéShon Peart; Sarha D’Haiti; Alana L. Grajewski; Mustafa Tekin; Ta Chen Chang; Guney Bademci (Scientific Reports)
Abstract Congenital anterior segment anomalies are disorders that affect the development of the eye and cause severe visual impairment. The molecular basis of congenital anterior segment anomalies is not well known. In this study, genome sequencing was performed on 27 families from diverse ethnicities with congenital anterior segment anomalies and 11 variants were identified, most of which were novel and family specific. These variants included single nucleotide variants CPAMD8:c.4825 C > T, c.534 G > A, CRYBB1:c.683 C > A, NHS:c.1180 C > T, GJA3:c.176 C > T, CRYGC:c.470 G > A, COL2A1:c.2819 G > A, c.1693 C > T, EPHA2:c.2864 A > C, a splice donor variant in COL11A1:c.933 + 1del, and a copy number variant in FBN1. The observed inheritance patterns were predominantly dominant, with a few recessive cases and a single instance of X-linked inheritance. Genome sequencing identified variants in 40.74% of diverse cases, offering valuable insights for enhancing the diagnosis and management of this disorder.